Original article Clinical significance of determining sST2 in the blood of patients with cardiac sarcoidosis - Marina V. Lebedeva; Leonid A. Strizhakov; Vladimir D. Beketov; Marina V. Taranova (LLC "MEDIAFORMAT", 2024)
The results of a pilot study of the serum marker of cardiac damage sST2 in patients with chronic generalized sarcoidosis are presented. Correlations between the activity of sarcoidosis, sST2 levels and the risk of developing heart failure have been demonstrated.